Association Between Upper-Extremity Health Condition and Depressive Status in an Elderly General Population. (16th December 2021) - Tajika, Tsuyoshi; Kuboi, Takuro; Oya, Noboru; Endo, Fumitaka; Shitara, Hitoshi; Ichinose, Tsuyoshi; Sasaki, Tsuyoshi; Hamano, Noritaka; Chikuda, Hirotaka
Background: This study was designed to investigate whether psychological status is associated with upper-extremity health status in an elderly general population. Methods: Using Quick Disabilities of the Arm, Shoulder, and Hand of the Japanese Society for Surgery of the Hand (QuickDASH-JSSH), we evaluated 200 Japanese elderly people (76 men, 124 women; mean age, 71.6 years, 60-98 years) to assess their upper-extremity-specific health status. Each had completed a self-administered questionnaire including gender and dominant hand items. As an indicator of hand muscle function, we measured their bilateral hand grip. Study participants were assessed for depressive symptoms using the Geriatric Depression Scale Short-Japanese Version (GDS-S-J). Statistical analyses were applied to clarify associations between self-assessed upper-extremity dysfunction and screening results for depressive symptoms in an elderly general population. Results: Those reporting no complaint of an upper extremity were 72 (36 men and 36 women) (36.0%). The GDS-J score was found to have significant positive correlation with age ( r = 0.20, P = 0.0045) and the QuickDASH score ( r = 0.25, P = 0.0004). The GDS-J score was found to have significant negative correlation with dominant grip ( r = −0.15, P = 0.04) and non-dominant grip strength ( r = −0.21, P = 0.004). For all participants, multiple regression analysis revealed the QuickDASH score as associated with the GDS-J score. Conclusion: Self-administered upper-extremity health condition as assessed using QuickDASH is correlated with depressive symptoms in elderly people. Objective pathophysiology and subjective illness behavior must be identified in daily clinical practice. A biopsychosocial approach must be used when advising and treating patients.